V.1 - Karim, Fazal (Delhi, 2006)
This book define on Judicial Review, contextually considered. the context is a written Constitution. The purpose of judicial review was ' to enforce the legal limits of public and in particular executive-power' the book contains, beside a fairly exhaustive study of the Constitutional concept of 'Judicial Power' a treatment of the constitutional concept of the 'Legislative Power' and the 'Executive Power' of the state.Included on interpretation is a chapter on tensions naturally arising out of the exercise of the power of Judicial Review.
Volume1 Judicial review of public actions
Keywords: Judicial review